Exploring Tutors’ Roles in Supporting Student Mental Health: Expectations and Perceptions in Higher Education - Rynke Douwes; Janneke Metselaar; Erik van der Meulen; Nynke Boonstra; Gerdina Hendrika Maria Pijnenborg (Education Sciences)
Student mental health is a challenging topic in higher education, with institutions aiming to develop policies and practices to support students’ personal and professional development. This study examined students’ expectations of their tutors regarding mental health support. An adaptation of the Mentor-Q questionnaire, focusing on tutor role perceptions, was used to measure student expectations. Confirmatory factor analysis showed a good fit of the adapted instrument. The questionnaire was completed by 869 students at a Dutch university of applied sciences, and the results were discussed with eight students. The findings revealed four role expectations of tutors: awareness raisers, connectors, referrers, and guardians. Latent class analysis revealed six clusters, with connector and referrer roles as well as awareness raiser and guardian roles being almost equally important within the clusters. The main difference between the clusters was the height of expectations. Satisfaction with the tutor was significantly related to cluster membership, such that higher expectations correlated with lower satisfaction. Additionally, students who discussed their mental health with their tutors were more represented in clusters with relatively low expectations. Discussions with the students highlighted the nuanced landscape of expectations and the importance of contextual factors and metacommunications. Implications for policy and practical development are also discussed.